Economic effects of migratory movements in the society of origin and in that of destination - García Sánchez, Alberto (2018)
In this article, we will discuss the economic consequences that the movement of people towards other countries entails. Therefore, we expose and analyze the main effects of migration in the society of origin and in the one of destination, both for household economies and for the whole of the population involved. We have relied on various studies that have attempted to shed light on this controversial subject in different parts of the world, although we have put emphasis on those that focused on Latin America. We hope this proposal will contribute to the current debate on the effects of migration.